Malaria risk and civil violence - Matteo Cervellati; Elena Esposito; Uwe Sunde; Simona Valmori (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
Using high-resolution data from Africa over the period 1998-2012, this paper investigates the hypothesis that a higher exposure to malaria increases the incidence of civil violence. The analysis uses panel data at the 1ê grid cell level at monthly frequency. The econometric identification exploits exogenous monthly within-grid-cell variation in weather conditions that are particularly suitable for malaria transmission. The analysis compares the effect across cells with different malaria exposure, which affects the resistance and immunity of the population to malaria outbreaks. The results document a robust effect of the occurrence of suitable conditions for malaria on civil violence. The effect is highest in areas with low levels of immunities to malaria. Malaria shocks mostly affect unorganized violence in terms of riots, protests, and confrontations between militias and civilians, rather than geo-strategic violence, and the effect spikes during short, labor-intensive harvesting periods of staple crops that are particularly important for the subsistence of the population. The paper ends with an evaluation of anti-malaria interventions.
urn:nbn:de:bvb:19-epub-36389-9
Keywords: D74; J1; 330; Malaria Risk; Civil Violence; Weather Shocks; Immunity; Cell-level Data; Africa